Efficient open-source implementations of linear-scaling polarizable embedding: use octrees to save the trees - Scheurer, Maximilian; Reinholdt, Peter; Olsen, Jógvan Magnus Haugaard; Dreuw, Andreas; Kongsted, Jacob (Journal of chemical theory and computation, 2021)
We present open-source implementations of the linear-scaling fast multipole method (FMM) within the polarizable embedding (PE) model for efficient treatment of large polarizable environments in computational spectroscopy simulations. The implementations are tested for accuracy, efficiency, and usability on model systems as well as more realistic biomolecular systems. We explain how FMM parameters affect the calculation of molecular properties and show that PE calculations employing FMM can be carried out in a black-box manner. The efficiency of the linear-scaling approach is demonstrated by simulating the UV/vis spectrum of a chromophore in an environment of more than 1 million polarizable sites. Our implementations are interfaced to several open-source quantum chemistry programs, making computational spectroscopy simulations within the PE model and FMM available to a large variety of methods and a broad user base.
Published online 5 May 2021
Published in issue 8 June 2021
Gesehen am 27.07.2021